Potensi limbah kulit dan biji rambutan (Nephelium lappaceum L) sebagai bioetanol - Johannes Martua Hutagalung; Galu Murdikaningrum; Melinda Yulianti; Shinta Nurcahyani (Composite : Jurnal Ilmu Pertanian, 2023)
In view of information on rambutan creation which is expanding, the misuse of rambutan strips and seeds is likewise expanding. Remembering that rambutan strips and seeds contain a few mixtures that can be utilized as elective unrefined components in the production of bioethanol. This study aims to determine the effect of variations in the addition of yeast on the yield and content of bioethanol, and also to determine the maximum mass of the addition of yeast to acquire the biggest yield and ethanol content. This research went through 5 stages, first stage is the readiness of the skin and seeds of rambutan, second stage is α-cellulose detachment, third step is hydrolysis with 1% HCl to create glucose which will be analyzed using Benedict's reagent and the Luff-Schoorl method. Qualitative analysis showed positive results and glucose levels obtained were 22.39% with a glucose yield of 1.50%. The fourth stage is glucose fermentation by using five days with variations in yeast weight of 5, 6 and 7 grams. The fifth step is to separate the resulting bioethanol by distillation and determine alcohol content using an alcohol refractometer. Yield bioethanol obtained by varying the weight of yeast 5, 6, and 7 grams respectively was 1.05%, 1.18%, and 1.67% with the levels of bioethanol obtained 1.95%, 2.15%, and 3.00%. The highest yield and content of bioethanol were obtained by adding 7 grams of yeast. The yield obtained on this bioethanol is 1.67% and the bioethanol content is 3.00%. Keywords: bioethanol, cellulose, fermentation, hydrolysis, rambutan peels.